Survei Keterlaksanaan Kurikulum Merdeka Mata Pelajaran Pendidikan Jasmani Olahraga dan Kesehatan (Pjok) pada Tingkat Satuan Pendidikan SMAN/SMKN Se-Kecamatan Driyorejo - Firman Yahya Simanjuntak; Faridha Nurhayati (Journal on Education, 2024)
The independent curriculum is the newest curriculum in Indonesia which changes traditional learning methods to encourage learning that is centered on students' abilities. It is implemented in all subjects, one of which is Education, Physical, Sports and Health (PJOK). The purpose of this research is to determine the implementation of PJOK learning in SMAN/SMKN in Driyorejo District using the Independent Curriculum and the supporting and inhibiting factors in implementing the independent curriculum. The method used in this research is a survey by distributing questionnaires to respondents. This research is a type of quantitative descriptive research. The population used was PJOK teachers and eleventh grade students at SMAN and SMKN Driyorejo and the research sample was the principal, deputy principal, five PJOK teachers, and two hundred and twenty-one students. The sampling technique applies cluster random sampling. Data analysis used percentage. Based on the research results, it can be explained that; 1) The implementation of the independent curriculum in PJOK subjects in SMAN and SMKN throughout Driyorejo District is in the "sufficient" category. Therefore, there are still several indicators or components that need to be improved for both teachers and students. 2) The factors that support the implementation of the independent curriculum at SMAN 1 Driyorejo and SMKN 1 Driyorejo are that the principal and head of curriculum support the continuous PJOK teacher training and development program regarding the implementation of the independent curriculum, and 3) the factor that hinders the implementation of the independent curriculum is that not all teachers understand learning flow in the independent curriculum.